1987
DOI: 10.1002/bit.260300813
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride‐promoted stereo selective hydrolysis of methyl‐2‐chloropropionate by lipase

Abstract: Esters of S-2-chloropropionic acid are important intermediates for synthesis of the active isomers (generally R-isomers) of many commercially important herbicides. While these esters are commercially available, their high cost is preventing their use in the synthesis of isomeric herbicides. There are several advantages of isomeric herbicides over their racemic counterparts. Among them, raw material cost reduction for the same activity, formulation cost reduction and lower mammalian toxicity. Cambou and Klibano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Naturally occurring phosphate solubilizing microorganisms have been recognized as a source of P fertilizer (Bhardwaj et al 2014). Several authors have reported a notable increase in yield of wheat and soybean through inocubation of P-solubilizing fungi (Kucey 1987(Kucey , 1988. Several phosphate solubilizing species of Penicillium have been evaluated for their plant growth promotion efficiency (Kucey 1988;Wakelin et al 2004), For instance, Penicillium bilaji inoculation increased P availability and uptaken by canola.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring phosphate solubilizing microorganisms have been recognized as a source of P fertilizer (Bhardwaj et al 2014). Several authors have reported a notable increase in yield of wheat and soybean through inocubation of P-solubilizing fungi (Kucey 1987(Kucey , 1988. Several phosphate solubilizing species of Penicillium have been evaluated for their plant growth promotion efficiency (Kucey 1988;Wakelin et al 2004), For instance, Penicillium bilaji inoculation increased P availability and uptaken by canola.…”
Section: Discussionmentioning
confidence: 99%
“…Lipases from different sources are widely used in different biochemical reactions such as esterification, transesterification, hydrolysis, alcoholysis, aminolysis, acidolysis, etc [7][8][9][10]. The hydrolysis of esters in the presence of water is a chemical reaction in which bond cleavage is affected by water to produce acid and alcohol, where water acts as nucleophile [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…C. cylindracea lipase is also used in this enantioselective hydrolysis (Cambou and Klivanov 1984a, b;Dahod and Siuta-Mangano 1987). Much of this effort has centred on the production of R-2-chloropropionic acid, due to its high value as an intermediate in the synthesis of herbicides.…”
Section: Introductionmentioning
confidence: 99%